Burden and epidemiology of status epilepticus in infants, children, and adolescents: A population‐based study on German health insurance data. (13th April 2019) - Schubert‐Bast, Susanne; Zöllner, Johann Philipp; Ansorge, Sonja; Hapfelmeier, Jana; Bonthapally, Vijayveer; Eldar‐Lissai, Adi; Rosenow, Felix; Strzelczyk, Adam
Summary: Objective: Status epilepticus (SE) is an important medical emergency condition with particularly unfavorable outcome in refractory and superrefractory SE (SRSE). The economic impact of SE and especially of SRSE in the pediatric population remains unclear. We aimed to determine the burden of illness of SE in a pediatric patient population. Methods: Insurance records for patients aged 0‐18 years admitted between 2008 and 2015 were selected from a nationwide insurance research database utilizing International Classification of Diseases and Related Health Problems, 10th Revision (ICD‐10) codes for SE (G41), epilepsy (G40), or febrile convulsions (R56). Patients were further classified based on admission to the intensive care unit and use of mechanical ventilation. Results: The algorithm identified 11 693 seizure‐related admissions and classified 4% as SE. Of these cases, 282 (60.4%) were classified by the algorithm as nonrefractory SE (NRSE), 125 (26.8%) as refractory SE (RSE), and 60 (12.8%) as SRSE. The crude SE incidence was 17.6/100 000, with NRSE being 11.4/100 000, RSE 3.9/100 000, and SRSE 2.3/100 000. SRSE incidence peaked in the 0‐ to 1‐year‐old age subgroup accounting for 48.3% of all pediatric SRSE admissions. The median length of stay (LOS) for all SE cases was 7 days, with median 44.5 days in SRSE, 5 days in NRSE, and 12 days in RSE. Mean admission costs for total SE were €15 880, with a mean expense for SRSE of €75 358, for NRSE of €4119, and for RSE of €13 864. The mean LOS for non‐SE epilepsy admissions was 3 days, with mean costs of €2697 for epilepsy and €1614 for febrile convulsion admissions. There were no deaths in non‐SE and NRSE admissions, whereas the overall mortality for SE was 3%, with 5.6% in RSE and 11.7% in SRSE. Significance: Although cases classified as SE represented 4% of the seizure‐associated admissions, they accounted for 22% of the overall costs. These costs were disproportionately represented by SRSE cases, which accounted for 62% of all SE‐associated costs.